A novel and improved method of predicting hand grip strength in the adult Malaysian population - Kamarul, Tunku; Ahmad, Tunku Sara; Loh, William Y.C. (Malaysian Medical Association, 2006)
Hand grip strength measurement is a recognized part of hand function assessment. The standard measurement using the Jamar dynamometer and comparing these results to the recommended normal values suggested by the manufacturers of the Jamar was questioned as these values were based on Western population. A study comparing a novel method of predicting grip strength using our software was conducted on 25 normal subjects using the LIDO kinetic workset (Group A and B ). These results were then compared against our predictive software (Group A) and the expected values supplied together with the Jamar Dynamometer (Group B). In another group, 22 normal subjects were tested using the Jamar (Group C and D) and then matched against the predicted values using their recommended chart (Group C). The last group (Group D) was tested using the Jamar but the values attained were compared to the results from our software. In group A, the predictability of our predictive method was 100% (both R & L) as compared to (R = 64%, L = 68%) in group B, (R = 27.3%, L = 59.1%) in group C and (R = 81.8%, L = 86.4%) in group D. The differences between the predictability of both methods were statistically significant. The data collected using both the Jamar and the LIDO kinetic workset correlated well to the data from our software but not to the values suggested by the manufacturers of Jamar. We conclude that our method of predicting hand grip values are superior to that suggested by the manufacturers of dynamometers. The standard reference for hand grip strength provided by the manufacturers is less accurate in predicting the grip strength of our local population.